2014
DOI: 10.3892/mmr.2014.3005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-nerve growth factor and homeobox A10 in experimental cryptorchidism treated with exogenous nerve growth factor

Abstract: With the exception of standard inguinal orchidopexy, treatment of cryptorchidism with human chorionic gonadotropin has been performed for several years; however, its side effects have limited its application. The β‑nerve growth factor (NGF) and homeobox A10 (HoxA10) genes are closely associated with the development of the testes. To the best of our knowledge, whether exogenous NGF alters the endogenous levels of NGF and HoxA10 in cryptorchidism in rats remains to be elucidated. The aim of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Epithelial ovarian cancer (EOC) is a major cause for malignancy-associated female mortality ( 1 ). The mortality rate is frequently increased by a delay in diagnosis and drug resistance ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial ovarian cancer (EOC) is a major cause for malignancy-associated female mortality ( 1 ). The mortality rate is frequently increased by a delay in diagnosis and drug resistance ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Satokata et al., (1995) ascertained that being localized solely to the gubernacular region of the male reproductive system, HOX10, when absent, caused cryptorchidism. Similarly, Xian et al., (2015) determined that, in rats, HOXA10 was localized to the germ, interstitial and Leydig cells of the testes and expressed at a lower level in cryptorchid testes. In another study conducted in mice by Bomgardner et al., (2003), it was found that HOXA10 was expressed in all regions of the epididymis and deferens.…”
Section: Discussionmentioning
confidence: 86%
“…To identify potential TFs driving conserved alternative promoter use in the three species, FIMO ( Grant et al, 2011 ) was used to predict the locations of TF-binding motifs in the MLT1F1 sequences, revealing a core “GTCATAAAA” sequence shared by all three species, predicted to bind to 14 TFs (Supplementary Figure S8). Among these TFs, HOX proteins are crucial for testicular and epididymal physiological functions and can affect male fertility ( Ferguson & Agoulnik, 2013 ; Topaloğlu et al, 2021 ; Xian et al, 2015 ). Species-conserved TE-derived alternative promoters were not limited to the same subfamily of TEs, i.e., different TE subfamilies acted on the same gene across the three species.…”
Section: Resultsmentioning
confidence: 99%